Cerințe legislative privind fabricatia și distribuția produselor medicinale veterinare. Alte produse din piața dedicate uzului veterinar - Marinela Panait (Medicamentul Veterinar, 2023)
The applicable legislative and regulatory field is an extremely dynamic one, constantly changing. In this PPT there is a presentation of the ways of harmonization with the EU internal market for veterinary medicinal products in the light of EU Regulation 6/2019. Creation, maintenance and use of unique databases at European level: UPD - Veterinary medicinal products - the single source of information on all authorized veterinary medicinal products and their availability in the member states of the European Union (EU) and the European Economic Area (EEA) . There is also a brief analysis of the trends in veterinary medicine production in Romania and what it means to develop a veterinary medicinal product.